Public family firms and economic inequality across societies - Jörn Block; Mirko Hirschmann; Tobias Kranz; Matthias Neuenkirch (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2022)
Research and public interest on economic inequality have grown over the last years. Family firms and the concentration of wealth and power in the hands of a few wealthy business families have been discussed as both a cause and a consequence of economic inequality. Yet, so far, we lack knowledge about the relationship between economic inequality and the share of family firms in an economy. Our study investigates how the share of family-controlled public firms correlates with various measures of income and wealth inequality. The results show that a higher share of public family-controlled firms leads to more income inequality in a country. This effect is particularly pronounced for the middle of the income distribution as opposed to the top quantiles. Redistribution only mitigates this effect to some extent, as the effect is significant for market income and disposable income. We also find that a higher share of family-controlled firms contributes to an increase in wealth inequality. Our results are of economic relevance as, for instance, a one standard deviation change in the share of family-controlled firms leads to an increase of around 1.4 percentage points in the Gini coefficients for market income, disposable income, and wealth.
Keywords: C50; D63; E00; L23; 330; Cross-country analysis; family firms; income inequality; wealth inequality